Hypoplastic myelodysplastic syndrome and acquired aplastic anemia: Immune-mediated bone marrow failure syndromes (Review) - Votavova, Hana; Belickova, Monika (International journal of oncology, 2022)
Hypoplastic myelodysplastic syndrome (hMDS) and aplastic anemia (AA) are rare hematopoietic disorders characterized by pancytopenia with hypoplastic bone marrow (BM). hMDS and idiopathic AA share overlapping clinicopathological features, making a diagnosis very difficult. The differential diagnosis is mainly based on the presence of dysgranulopoiesis, dysmegakaryocytopoiesis, an increased percentage of blasts, and abnormal karyotype, all favouring the diagnosis of hMDS. An accurate diagnosis has important clinical implications, as the prognosis and treatment can be quite different for these diseases. Patients with hMDS have a greater risk of neoplastic progression, a shorter survival time and a lower response to immunosuppressive therapy compared with patients with AA. There is compelling evidence that these distinct clinical entities share a common pathophysiology based on the damage of hematopoietic stem and progenitor cells (HSPCs) by cytotoxic T cells. Expanded T cells overproduce proinflammatory cytokines (interferon‐γ and tumor necrosis factor‐α), resulting in decreased proliferation and increased apoptosis of HSPCs. The antigens that trigger this abnormal immune response are not known, but potential candidates have been suggested, including Wilms tumor protein 1 and human leukocyte antigen class I molecules. Our understanding of the molecular pathogenesis of these BM failure syndromes has been improved by next‐generation sequencing, which has enabled the identification of a large spectrum of mutations. It has also brought new challenges, such as the interpretation of variants of uncertain significance and clonal hematopoiesis of indeterminate potential. The present review discusses the main clinicopathological differences between hMDS and acquired AA, focuses on the molecular background and highlights the importance of molecular testing.
Keywords: prognóza; imunita; Prognosis; Myelodysplastic-Myeloproliferative Diseases; lidé; Bone Marrow Failure Disorders; Anemia, Hemolytic, Autoimmune; syndromy selhání kostní dřeně; Immunity; autoimunitní hemolytická anemie; myelodysplasticko-myeloproliferativní nemoci; Humans